Trends in the development and use of interactive multimedia for physics learning: a systematic literature review - Jamiatul Ummah; Sutopo; Nandang Mufti; Musbau Dogo Abdulrahaman (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2025)
While research on interactive multimedia in physics education is abundant, a systematic review of its development and implementation trends remains scarce. This study aims to address this gap by investigating these trends through a Systematic Literature Review (SLR) with the PRISMA stages using bibliometric analysis. A total of 32 scientific articles from 2016–2025 were selected based on the Scopus (Q1–Q4) and SINTA (1–3) indexes to ensure quality and reliability. The results of the study show that the use of interactive multimedia fluctuates, with a significant spike in 2020 due to the COVID-19 pandemic which encouraged online learning. The impact of the use of interactive multimedia in physics learning is very diverse, along with the development of technology that allows for increasingly sophisticated and varied multimedia designs. The most widely studied physics topic is mechanics, given its role as a basis for understanding other physics topics. The implications of this study indicate that SLR research is capable of providing an up-to-date mapping of the development of interactive multimedia in physics learning while revealing research gaps, particularly the limited integration of artificial intelligence (AI) and testing of the effectiveness of multimedia implementation, as well as the lack of research studies using interactive multimedia in physics subjects such as temperature-heat and momentum-impulse.